PSYCHOLOGICAL AND PEDAGOGICAL ANALYSIS OF THE FORMATION OF THE CATEGORY OF "SELF-ANALYSIS" (Pedagogy of Higher and Secondary Education, 2022)
The main aspects of psychological-and-pedagogical analysis of “self-analysis” category, approaches to conceptions defining are illuminated in the article. It is clarified that in the context of inventing specific pedagogical conditions for a future teacher’s self-analysis activity formation it is extremely important to define as a result of “self-analysis” activity not only students’ cumulative presentations about themselves but also their cumulative experience in “self-analysis” activity and its significance as well.
Keywords: introspection; self-analytical activity